Beyond stereotypes: Comparing Chinese and Australian parents' perceptions of transition to school. Issue 1 (March 2022) - Liu, Liwei; O'Gorman, Lyndal; Dillon-Wallace, Julie; Petriwskyj, Anne
Parents' perceptions and expectations of transition to school influence their engagement in the transition process. In this study, eight Chinese and eight Australian parents were interviewed to explore their perceptions of transition to school. The results showed similarities in Chinese and Australian parents' views of transition to school as a two-phase process involving preparation and school familiarisation. Cohort and intra-cohort differences were evident in the type of preparation, attention to diverse needs and the difficulty of the transition process. Moreover, Australian, but not Chinese, parents regarded transition to school as a change for themselves. The findings challenge stereotypes, indicating the need for more reciprocal communication to address parent expectations about transition to school in diverse communities.